UTILIZATION OF INDUSTRIAL WASTE (FLY ASH) AND COW DUNG PROPORTIONS ON THE GROWTH ACTIVITY OF EARTHWORM (Eudrilus eugeniae) DURING VERMICULTURE - PRADHAN, TEJASWINI; SATAPATHY, SUNITA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
This paper presents investigation on the process of vermiculture by the action of Eudrillus eugeniae with population growth with the utilization of fly ash and cow dung during vermicomposting. Like several industrial wastes a large scale generation of Fly Ash is one of generated from thermal power plants is now posing an acute global problem for its disposal. Recycling of FA is now being paid attention by using biological method to prevent it from contamination of the land and underground water. Broadly speaking, Fly Ash (FA) contains some heavy toxic metals, such as lead, arsenic, mercury, cadmium, and uranium. Vermicomposting is a promising technology for improving the nutrient status of FA for enhancing it’s applications in agricultural sectors. The introduction of earthworm Eudrilus eugeniae into various treated containers FA to accumulate heavy metals into plant nutrient were properly monitored with it’s growth activity, survival of species and formation of vermicasts as the end product during the entire process of vermicomposting through different physic-chemical analysis like pH, electro-conductivity(EC). The vermicomposting process has been carried out with the proportions as Fly Ash (FA) of 20%, 40% of soil and 60% of cow 7dung.